Loss of ATRX and DAXX expression identifies poor prognosis for smooth muscle tumours of uncertain malignant potential and early stage uterine leiomyosarcoma. (16th March 2015) - Slatter, Tania L.; Hsia, Howard; Samaranayaka, Ari; Sykes, Peter; Clow, William (Bill); Devenish, Celia J.; Sutton, Tim; Royds, Janice A.; PC, Philip; Cheung, Annie N.; Hung, Noelyn Anne
Abstract: Uterine smooth muscle tumours of uncertain malignant potential (STUMP) are diagnostically and clinically challenging. The alternative lengthening of telomeres (ALT) telomere maintenance mechanism is associated with poor survival in soft tissue leiomyosarcoma. Time to first recurrence and survival were known for 18 STUMP and 43 leiomyosarcomata (LMS). These were screened for ALT telomere maintenance by the presence of ALT‐associated PML bodies (APBs) and for changes associated with the ALT phenotype, namely aberrant p53 expression, isocitrate dehydrogenase 1 mutation (R132H substitution) expression, mutant ATRX (αthalassemia/mental retardation syndrome X‐linked) expression and mutant DAXX (death‐domain‐associated protein) expression by immunohistochemistry (IHC). Overexpression of p16 INK4A was examined immunohistologically in a subset of cases. Many of the tumours associated with death or recurrence demonstrated APBs commensurate with ALT telomere maintenance. However, all uterine STUMP (4/4), and vaginal STUMP (2/2) patients, and almost all LMS patients (88.4%, 23/26, including 90% (9/10) of stage 1 LMS cases), who had died of disease or who had recurrent disease, displayed loss of ATRX or DAXX expression. Loss of ATRX or DAXX expression identified poor prognosis (95% CI 2.1 to 40.8, p < 0.003), in the LMS group. Thus, loss of ATRX or DAXX expression in uterine smooth muscle tumours identifies a clinically aggressive molecular subtype of early stage LMS and when histopathological features are problematic such as in STUMP. As ATRX and DAXX IHC is readily performed in diagnostic laboratories these are potentially useful for routine histopathological classification and management.